2/3m-7=4/3m+3

Simple and best practice solution for 2/3m-7=4/3m+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3m-7=4/3m+3 equation:



2/3m-7=4/3m+3
We move all terms to the left:
2/3m-7-(4/3m+3)=0
Domain of the equation: 3m!=0
m!=0/3
m!=0
m∈R
Domain of the equation: 3m+3)!=0
m∈R
We get rid of parentheses
2/3m-4/3m-3-7=0
We multiply all the terms by the denominator
-3*3m-7*3m+2-4=0
We add all the numbers together, and all the variables
-3*3m-7*3m-2=0
Wy multiply elements
-9m-21m-2=0
We add all the numbers together, and all the variables
-30m-2=0
We move all terms containing m to the left, all other terms to the right
-30m=2
m=2/-30
m=-1/15

See similar equations:

| 36.3y=12.1;2.3.4 | | 55+x=25 | | 30+x+2x-12=72 | | 3x+3-2=x+6 | | 2/3(x-7)=2 | | 5x=6,5-(x-5)² | | 7+x/0.5=2 | | 5m+30=-2m-19 | | 1/2(x-5)(x-14)=35 | | X(2-√2)=(4-x)(x²-x) | | 9=3/2v | | 7/6x=1/6 | | 6t+10=5 | | 2(x-1)+4=7(2x+3)-5 | | d5.5=4;22.23.24 | | 2x+35=5x-7 | | 27=y/3-16 | | 2^x=18^6 | | w/9=0.9 | | 3-(1-2x)=10-x | | 7.5h+10=6.25(h−3) | | k^2=0.49k | | 7.5h=6.25(h−3)+10 | | 6(x-4)+7=2(x+4) | | 11+3x-3=8x+7-5x | | 2x+31=(x+13)+7 | | –9u=45 | | 7p-1=5 | | 4.5x=18;3.4.5 | | 6(x−4)+7=2(x+4) | | 5(2x-1)=x+6 | | 20a-8a-16a14a+18a=16 |

Equations solver categories